Not a Shift in Lineage but a Shift in Responsibility: The Concept of Kafālah in the Care of Adopted Children from an Islamic Legal Perspective - Yusnadia Achda Saputri; Kurniati (Jurnal Studi Gender dan Anak, 2025)
This study examines the forms of covert psychological violence experienced by adopted children in foster families and explores the implementation of the concept of kafālah in Islamic law to protect them. Adopted children are often vulnerable to psychological pressure and exploitation because their relationship with their foster family, which has no blood ties, is often considered a disadvantageous distinguishing factor. Based on the principle of kafālah, adopted children retain their rights to identity and care. The research method used a qualitative approach with a literature study method to understand the forms of psychological abuse experienced by adopted children in their adoptive families. The results show that neglect and psychological abuse of adopted children often occur covertly, causing long-term trauma. The implementation of the kafālah concept is proposed as a solution to ensure the protection of the emotional rights of adopted children, emphasizing the importance of the role of adoptive parents in creating a safe and supportive environment for them. This study is expected to raise public awareness and encourage the application of appropriate kafālah principles so that the psychological well-being of adopted children is better guaranteed. [Penelitian ini mengkaji bentuk-bentuk kekerasan psikologis terselubung yang dialami oleh anak angkat dalam keluarga angkat serta mengeksplorasi implementasi konsep kafālah dalam hukum Islam untuk melindungi mereka. Anak angkat kerap kali rentan terhadap tekanan psikologis dan eksploitasi, karena hubungan mereka yang tidak memiliki ikatan darah dengan keluarga angkat sering dianggap sebagai faktor pembeda yang merugikan. Berdasarkan prinsip kafalah, anak angkat tetap memiliki hak identitas dan perawatan yang terjaga. Metode penelitian menggunakan pendekatan kualitatif dengan metode studi literatur untuk memahami bentuk-bentuk kekerasan psikologis yang dialami oleh anak angkat dalam keluarga angkat. Hasil penelitian menunjukkan bahwa pengabaian dan kekerasan psikologis terhadap anak angkat seringkali terjadi secara tersembunyi, yang dapat menimbulkan trauma jangka panjang. Implementasi konsep kafālah diusulkan sebagai solusi untuk memastikan perlindungan hak-hak emosional anak angkat, menekankan pentingnya peran orang tua angkat dalam menciptakan lingkungan yang aman dan mendukung. Penelitian ini diharapkan dapat meningkatkan kesadaran masyarakat dan mendorong penerapan prinsip kafālah yang sesuai, sehingga kesejahteraan psikologis anak angkat lebih terjamin].